Multisensory Tristram Shandy. Issue 3 (December 2016) - Malone, Cynthia Northcutt
Abstract : An absorbed reader typically pays little conscious attention to the visual, tactile, and sometimes aural sensory experiences of reading. Unexpected formal and visual features of Laurence Sterne's nine-volume fictional narrative, The Life and Opinions of Tristram Shandy, Gentleman, startle readers out of absorption and call attention to familiar operations like decoding black figures on white paper and turning pages. My edition of Volume I is designed to engage the senses through its visual structure, textures, and unexpected materials (buttons, marbled paper strips, and ribbons) and through formal surprises (interpolated documents, accordion-fold inserts, and paper lace). In its structure and materials, this edition highlights the odd formal features of Sterne's novel and the cognitive work that the narrator requires of earnest and industrious readers.